THE LAPLACIAN SPECTRUM AND SEIDEL SPECTRUM OF SUNFLOWER HYPERGRAPHS S(a, m, n) - Yana Putri, Melani
Let H(V, E) be a hypergraph with a vertex set V and an edge set ". In this thesis, one type of a hypergraph, namely sun ower hypergraph S(a; m; n), is investigated. The Laplacian spectrum of the sun ower hypergraph S(a; m; n) gives that the sun ower hypergraph S(a; m; n) is a Laplacian integral hyper- graph. The necessary and sufficient conditions for the sun ower hypergraph S(a; m; n) to be a Seidel integral hypergraph are given. Moreover, the Laplacian energy and Seidel energy for a sun ower hypergraph S(a; m; n) are also defined.